Is the risk of cervical atypia associated with the interval between menarche and the start of sexual activity? A population-based cohort study. Issue 9 (11th September 2019) - Adhikari, Indira; Eriksson, Tiina; Luostarinen, Tapio; Apter, Dan; Lehtinen, Matti
Abstract : Objective: We investigated whether the risk of cervical atypia is associated with a short interval between the age at first sexual intercourse (FSI) or age at the start of oral contraceptive (OC) use and menarche. Design: A population-based cohort study. Setting: Finnish women in the age range of 16–17 years old were enrolled in the PATRICIA trial of human papillomavirus (HPV) 16/18 vaccine efficacy. Participants: The association of cervical atypia with the interval between FSI or start of OC use and menarche was assessed in the control arm (hepatitis A vaccinated) who had participated in biannual clinical follow-up visits for 4 years. Altogether, 913 women had normal baseline cervical cytology and answered behavioural questionnaires at enrolment and end of the follow-up. Main outcome measure: ORs with 95% CIs using univariate and multivariable logistic regression were used to assess the association between cervical atypia and the interval between FSI or the start of OC use and menarche. Results: The mean ages at menarche, FSI and the start of OC use were 12.4, 16.0 and 16.4. Chlamydia trachomatis infection was associated with an increased risk of cervical atypia in women with a short (<3 years) interval between menarche and FSI/start of OC use (OR 1.8, 95% CI 1.0 to 3.6 and OR 2.2, 95% CI 1.0 to 5.1). Whereas HPV 16/18 infection was associated with increased atypia risk estimates in women with a longer (≥3 years) interval (OR 1.8, 95% CI 1.1 to 2.7 and OR 1.4, 95% CI 1.0 to 2.1). In women with a short interval between menarche and FSI, early age at the start of OC use was not associated with an increased risk of cervical atypia in the univariate (OR 0.7) nor multivariable analyses. Conclusion: Short interval between menarche and the age at start of sexual activity does not increase the risk of HPV-associated cervical atypia. Trial registration number: NCT00122681 .